Phrase Types and Their Meanings in Laneige’s Skincare Product Detail Slogans - Gillian Cresentia Rachelin; Herwindy Maria Tedjaatmadja (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study analyzes both the types of phrase and the types of meaning found in Laneige’s skincare product detail slogans using Biber et al.’s (1999) types of phrase and Leech’s (1981) types of meaning. Using a qualitative approach, the study reveals that 23 slogans convey five types of phrase and five types of meaning. Noun phrases and prepositional phrases are the most common types of phrase, while affective meaning and conceptual meaning are the most common types of meaning. Verb phrases and adverb phrases, as well as social meaning and thematic meaning were not present. The use of noun phrase and affective meaning effectively highlights the product benefits and the positive attributes of the skincare products.